VCS450: Culture and Personality Development / College of Creative Arts - UiTM, College of Creative Arts (2023)
This course exposes to the students the basic concept of art, development of culture and personality. The discussion cover the introduction to personality development, the influence of personality traits, art and culture, social and behavior culture, the Five-factor Theory, the Five-factor Model, art and social values and using inventory in personality development. Understanding personality traits ultimately would contribute to be well versed with the people and their culture. This subject also emphasizes on sharing students' experience and knowledge; thus, stimulate the students' ability of analyzing personality traits in culture.